Age at menarche and the menstrual pattern of secondary school adolescents in central India - Ambade, Rakhee; Sagdeo, Mohan (International Journal of Research in Medical Sciences, 2017)
Background: Population studies on characteristics of menstrual cycles are scarce. Knowledge on this variability is necessary for patient education and to guide clinical evaluation. Methods: A cross sectional study was conducted and 622 school girls were selected randomly. A pretested questionnaire was used to gather data. Results: Mean age of participants was 16.9 ± 1 years. About 92.2% had attained menarche. Probit analysis of the status-quo data yielded median age at menarche of 14.8 (13.9-15.3) years and by recall method to be 15.8 ± 1 years. The mean age at menarche was, significantly, 0.3 years younger for urban females compared with rural ones. Cycle length between 21-35 days was observed in 70.3% of the girls. Mean duration of flow was 4 ± 1.3 days. Menstrual cycles were irregular in 42.8% of the subjects. Overall prevalence of dysmenorrhoea was 72%. and of PMS was 75.4%. Conclusions: Age of menarche was found to be significantly delayed. Considerable number of students complained of dysmenorrhoea and premenstrual symptoms.